PERANCANGAN SISTEM PENGENALAN INFORMASI DESTINASI WISATA CURUG DI KAKI GUNUNG SALAK - Dendy Kurniawan; Abel Krisna Hogantara; Ahmad Fauzi; Andi Dwi Pangestu (CV. Denasya Smart Publisher, 2024)
The purpose of this study is to assist tourists in providing information on tourist services for the waterfall at the foot of Mount Salak, so as to produce precise and accurate information reports. The development method used in this research is the SDLC (System Development Life Cycle) system. SDLC System Development Method This SDLC method is a method with a system development and design process through several stages, starting from system planning to operation and maintenance. Data collection methods used in this study are: observation, interviews, and literature study. This research produces an application that can assist tourists in providing more accurate information on waterfall tourism services at the foot of Mount Salak.